PERSEPSI DAN KESIAPAN MAHASISWA DALAM PENGGUNAAN ACCURATE MELALUI SISTEM CLOUD ACCOUNTING DENGAN PENDEKATAN TAM (TECHNOLOGY ACCEPTANCE MODEL) - Syifa Salsabila Izani (2021)
The research objective is to test students perceptions and readiness in using accurate through a cloud accounting system with a TAM (technology acceptance model) approach. Survey with the object of accounting students at the Veterans National Development University Jakarta for the 2020/2021 academic year who have used accurate, with the measurement of constructs of computer self efficacy, perceived usefulness, perceived ease of use, attitude toward using, behavioral intentions, and actual use of accurate accounting software, using a questionnaire instrument for primary data collection on a sample of 60 students. The results of the analysis using structural equation modeling - partial least squares. shows that the ability to use computers (CSE) has no effect on perceived usefulness (POU). The ability to use a computer (CSE) has a positive effect on the perceived ease of use (PEU) of accounting software. Perceived ease of use (PEU) has a positive effect on perceived usefulness (POU) of accounting software. Perceived usefulness (POU) has a negative or no effect on user attitudes (ATU) of accounting software. Perception of ease of use (PEU) has a negative or no effect on user attitudes (ATU) of accounting software. Perceived usefulness (POU) has a positive effect on behavioral interest (BEI). User attitudes (ATU) of accounting software have a negative or no effect on behavioral interest (BEI). Behavioral interest (BEI) has a positive effect on the actual use (ACU) of accounting software.